Killing pigs and talking to nonna: "wog" versus "cosmopolitan" Italianitá among second-generation Italian-Australians and the role of family. Issue 10 (27th July 2019) - Sala, Emanuela; Baldassar, Loretta
ABSTRACT: This paper extends the literature on second-generation migrants by examining the construction of ethnicity (Italianitá) over time. We compare two cohorts of second-generation Italian-Australians: the post-World War II cohort and the post-1980s cohort. Ethnographic data for this research were collected with second-generation Italian-Australians in Perth over a thirty-year period. Our findings highlight important differences between these two groups based on socio-historical context and transnational experiences. Informants draw on these differences to distinguish between "wog" vs. "cosmopolitan" forms of Italianitá. While these contrasting identities highlight cultural discontinuities between cohorts, both groups construct their ethnicity through the trope of the Italian migrant family. Employing the theoretical notions of "intimate culture" and "familial habitus" we theorize family as integral to conceptualizations of ethnic field and show how it has been overlooked and devalued in analyses of diaspora politics and identity.